"Which mouse kissed the frog?" Effects of age of onset, length of exposure, and knowledge of case marking on the comprehension of wh-questions in German-speaking simultaneous and early sequential bilingual children*. Issue 3 (29th February 2016) - ROESCH, ANNE DOROTHEE; CHONDROGIANNI, VASILIKI
Abstract: Studies examining age of onset (AoO) effects in childhood bilingualism have provided mixed results as to whether early sequential bilingual children (eL2) differ from simultaneous bilingual children (2L1) and L2 children on the acquisition of morphosyntax. Differences between the three groups have been attributed to other factors such as length of exposure (LoE), language abilities, and the phenomenon to be acquired. The present study investigates whether four- to five-year-old German-speaking eL2 children differ from 2L1 children on the acquisition of wh -questions, and whether these differences can be explained by AoO, LoE, and/or knowledge of case marking. The 2L1 children outperformed the eL2 children in terms of accuracy; however, both bilingual groups exhibited similar error patterns. This suggests that 2L1 and eL2 bilingual children are sensitive to the same morphosyntactic cues, when comprehending wh -questions. Finally, children's performance on the different types of wh -questions was explained by a combination of knowledge of case marking, LoE, and AoO.